Proinflammatory Differentiation of Macrophages Through Microparticles That Form Immune Complexes Leads to T- and B-Cell Activation in Systemic Autoimmune Diseases - Burbano, Catalina; Villar-Vesga, Juan; Vásquez, Gloria; Muñoz-Vahos, Carlos; Rojas, Mauricio; Castaño, Diana (Frontiers in Immunology, 2019)
Patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) demonstrate increased circulating microparticles (MP). These vesicles, primarily those that form immune complexes (MP-IC), may activate monocytes. We evaluated the effect of MP and MP-IC in the differentiation of monocytes to macrophages (monocyte-derived macrophages; MDM) and for consequences in autologous lymphocyte activation. Monocytes from healthy controls (HC) and patients with RA and SLE that differentiated into MDM in the presence of MP-IC showed a proinflammatory (M1-like) profile, which was more evident using MP-IC from patients with RA than those from patients with SLE. Notably, MDM from HC and patients with RA that differentiated with MP-IC were more prone to M1-like profile than those from patients with SLE. In HC and patients with RA, monocyte differentiation using MP-IC decreased the frequency of MDM that bound/internalised latex beads. The M1-like profile did not completely revert following IL-4 treatment. The effect of M1-like MDM on T lymphocytes stimulated with phytohemagglutinin was further evaluated. MDM differentiated with MP enhanced the proliferation of T cells obtained from patients with RA compared with those differentiated with MP-IC or without vesicles. Neither MP nor MP-IC induced interferon (IFN)-+ and tumour necrosis factor (TNF)-+ T cells in patients with RA. Conversely, unlike MDM differentiated with or without MP, MP-IC enhanced the proliferation and increased the frequencies of IFN-g+CD4+ T, TNF-a+CD4+ T and IFN-g+CD8+ T cells in patients with SLE. The co-culture of B cells with MDM obtained from patients with RA and SLE and differentiated with MP-IC increased the expression of B-cell activation markers and prevented B lymphocyte death. Strikingly, only for patients with SLE, these responses seemed to be associated with a significant increase in B-cell activating factor levels, high plasmablast frequency and immunoglobulin production. These results showed that MP-IC from patients with systemic autoimmune diseases favoured the polarisation of MDM into a proinflammatory profile that promotes T-cell activation , and additionally induced B-cell activation and survival. Therefore, the effect of MP-IC in mononuclear phagocytes may be an important factor for modulating adaptive responses in systemic autoimmune diseases.